Analysis of gear surface morphology based on gray level co-occurrence matrix and fractal dimension - Wei, Bo; Zhao, Xiaofang; Wang, Long; Hu, Bin; Yu, Lei; Tang, Hongwei (PloS one, 2019)
To investigate morphological characteristics and generation mechanism of the machined gears surface, image characteristics of machined surface morphology including profile roughness, fractal and textural characteristics were studied. the change of profile curves for the surface image is subject to the normal probability density function and the W-M function. The orientation angle of surface texture is 0°, the surface profile curves are the smoothest and have the most uniform, regular textures. When the texture orientation is 45° or 135°, the surface profile curves show large fluctuations, while surface image textures present the deepest grooves and are shown to be distributed most irregularly. Additionally, the influence mechanism of different grinding parameters on the morphological characteristics of machined surface was investigated. The quality of machined surfaces increased with the grinding speed while deteriorated with increasing radial, or axial, feed speeds.